An Analytical Research on the Impact of Employee Poaching on Turnover Intention Among Private University - Marisi Butarbutar; Elly Romy; Ramesh Krishnan; Acai Sudirman (Jurnal Organisasi dan Manajemen, 2025)
Purpose – This research analyzed the relationship model between employee poaching, career development, work-life balance, job satisfaction, and turnover intention in private university lecturers in North Sumatra. Methodology – Data was collected through an online survey using a structured questionnaire sent to lecturers working at various regional private universities. The number of samples explored was 200 lecturers. Following the process, path analysis methods using Structural Equation Modeling (SEM) were used to test the proposed relationship model. Results – The results showed that employee poaching, work-life balance, and job satisfaction had a positive and significant effect on turnover intention. Meanwhile, other research results found that career development had a positive and not significant effect on turnover intention. Originality – The results provided valuable perception for private higher education management in understanding the factors that influenced turnover intention of lecturers and developing effective strategies to retain as well as increase satisfaction and retention of lecturers. The results of this analysis also contributed to human resource management research and literature, specifically in the context of higher education in Indonesia. By paying attention to these factors, higher education institutions can maintain and increase retention of lecturers and improve the general quality of higher education in the North Sumatra region.